The Concept of Social Rehabilitation and its Elements in the Transfer of Prisoners for Further Execution of a Custodial Sentence - Markevičiūtė, Ugnė (Teisė, 2021)
This article analyses the origins of the aim of social rehabilitation in the transfer of prisoners for further execution of a custodial sentence, elements of social rehabilitation, and its concept, which is not explicitly defined at the European Union level. In order to deliver a more thorough analysis of social rehabilitation elements, special attention is given to the relevant Lithuanian legislation and jurisprudence regarding the elements of social rehabilitation and their assessment.